Réponses

  • Omnes
  • Modérateur confirmé
2014-02-01T16:55:13+01:00
Salut,

Exercice 2,
1)
 \frac{2x-3}{5} =  \frac{1-2x}{3} \\
\frac{2x-3}{5} - \frac{1-2x}{3} = 0 \\
 \frac{6x - 9 - (5 - 10x) }{15} = 0 \\
 \frac{6x - 9 - 5 + 10x}{15} = 0 \\
 \frac{16x - 14}{15}  = 0 \\
16x - 14 = 0 \\
16x = 14 \\
x =  \frac{14}{16} \\
x =  \frac{7}{8}
2)
 \frac{x}{3} - 1 =  \frac{3}{2}  -  \frac{3x}{4} \\
 \frac{x - 3}{3} =  \frac{18+9x}{12} \\
 \frac{4x - 12 - 18 - 9x}{12} = 0 \\
 \frac{-5x - 30}{12} = 0 \\ -5x - 30 = 0 \\ -5x = 30 \\
x =  \frac{30}{-5}  
\\ x = -6
3)  \frac{2x - 5}{5} +  \frac{2-5x}{3} =  \frac{7 - x }{2} -  \frac{3x - 2}{10} -  \frac{1}{30}\\
 \frac{12x - 30 + 20 - 50x }{30}  =  \frac{105 - 15x - (9x - 6) - 1}{30} \\
 \frac{-38x -10}{30} =  \frac{110 -24x}{30} \\
 \frac{-38x - 10 - 110 + 24x}{30}  = 0\\
-14x -120 = 0 \\
-14x = 120 \\
x =  \frac{120}{-14} \\
x =  -\frac{60}{7}
4) [tex] \frac{5x - 1}{7} - \frac{4+3x}{3} = \frac{-x+8}{2} - \frac{3x-1}{6} \\ \frac{15x - 3 - 28 -21x}{21} = \frac{-6x + 48 - 6x + 2}{12} \\ \frac{-6x - 21}{21} = \frac{-12x + 5}{12} \\ \frac{-2x - 7 }{3} = \frac{-12x + 5}{12} \\ \frac{-8x - 28 - (-12x + 50)}{12} = \\ -8x - 28 +12x - 50 = 0 \\ 4x = 78 \\ x = \frac{78}{4} \\ x = \frac{39}{2} [/tex]